Digital Humanities at the Crossroads between Museums and Tourism - Roque, Maria Isabel (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2015)
The dialogue between museum and public faces an increasingly challenge, with the growth of cultural tourism, seen as prestigious leisure activity, which allows it to select some destinations, meanwhile others are abandoned. There are new forms of development related to creative tourism, requiring the redefinition of museum activities in association with the other cultural experiences on territory. The relationship between tourism and museum involves the research in digital humanities. The application of technology may enhance the visitor's museum experience. It anticipates the collection knowledge and helps to prepare the museum visit, according to its expectations and experiences. In the museum, it allows him to interact with the exhibition and to access to the additional cognitive resources, and it provides the functional and symbolic context of the object. Finally, after the visit, it restores the memories of the experience. The museum takes back the mediating role as cultural and leisure space, in order to accomplish the creative tourism requirements.